(untitled) (Nigerian Journal of Physiological Sciences, 2024)
Hydrocephalus, the aberrant enlargement of the brain’s ventricles, is caused by a build-up of cerebrospinal fluid that stretches the periventricular white matter and may disrupt the connections between the pyramidal neurons in the cerebral cortex. Using an intra-cisternal kaolin injection hydrocephalic rat model, we aimed to determine if the effects of hydrocephalus on the white matter will subsequently impact the dendrites of cortical pyramidal neurons, which are the synaptic sites for the white matter fibres, particularly the afferent fibres. Three-week-old hydrocephalic rats were compared with controls after 1 week, 2 weeks and 4 weeks. Dendritic arborisations of the pyramidal neurons were evaluated using a modified Golgi stain. Haematoxylin and Eosin, and Cresyl violet stains were used to measure cortical thickness and pyramidal neuronal count. The hydrocephalic rats’ cerebral cortex and corpus callosum were thinner (p<0.0001) than the controls. Rats with hydrocephalus had a similar pyramidal neuron count to the controls, with no significant decline. After two weeks of hydrocephalic induction, the pyramidal neurons’ dendritic branching changed due to basal dendritic reduction and denudation. Reduced thickness in the corpus callosum and sensorimotor cortex was observed in the hydrocephalus animals. The pyramidal cell population remained unaffected, but the basal dendrites of the cells were substantially weakened. Ventricular enlargements during the juvenile developmental stage may harm dendritic arborization, which could obstruct neurological maturation.